2016
DOI: 10.1016/j.celrep.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRas-Induced Mitochondrial Oxidative Stress in Acinar Cells Upregulates EGFR Signaling to Drive Formation of Pancreatic Precancerous Lesions

Abstract: SUMMARY The development of pancreatic cancer requires the acquisition of oncogenic Kras mutations and up-regulation of growth factor signaling, but the relationship between these is not well established. We here show that mutant Kras alters mitochondrial metabolism in pancreatic acinar cells, resulting in increased generation of mitochondrial reactive oxygen species (mROS). Mitochondrial ROS then drives the dedifferentiation of acinar cells to a duct-like progenitor phenotype and progression to PanIN. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
241
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(249 citation statements)
references
References 42 publications
8
241
0
Order By: Relevance
“…During PanIN de-differentiation KRAS mutations in acinar cells have been shown to drive PKD1-dependent mitochondrial ROS increases and that this event is the leading factor responsible for EGFR-mediated ADAM17 shedding 43 . Similarly, in KRAS mutant colorectal cancer, inhibition of the PI3K/mTOR pathway sensitizes cells to EGFR inhibitors 8 .…”
Section: Evs Reprogram Cancer Cell Metabolismmentioning
confidence: 99%
“…During PanIN de-differentiation KRAS mutations in acinar cells have been shown to drive PKD1-dependent mitochondrial ROS increases and that this event is the leading factor responsible for EGFR-mediated ADAM17 shedding 43 . Similarly, in KRAS mutant colorectal cancer, inhibition of the PI3K/mTOR pathway sensitizes cells to EGFR inhibitors 8 .…”
Section: Evs Reprogram Cancer Cell Metabolismmentioning
confidence: 99%
“…1 Approximately 95% of all pancreatic ductal adenocarcinoma (PDA) show acquisition of activating KRAS mutations, 2 which, due to oncogene-mediated alterations in the cell's metabolism, goes along with increased cellular oxidative stress levels. [3][4][5][6] In mouse models for development of PDA, KRas-caused formation of ROS already is induced in acinar cells and gradually increased during ADM and PanIN formation and progression 5 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These include activation of the ERK1/2 signaling pathway, 6 upregulation of epidermal growth factor receptor (EGF-R) signaling, 5 as well as induction of canonical and alternative activation pathways for nuclear factor k-B (NF-kB), 5 which both have been implicated in the progression of PDA. 20,21 The serine/threonine kinase Protein Kinase D1 (PKD1) is a major mediator of KRas-mROS signaling, 5,22 however, its activation by mROS most likely is indirect. Previously, it was shown that in response to mROS PKD1 can be activated via Src-mediated phosphorylation…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations